ETHNOMEDICINAL, PHYTOCHEMICAL CONSTITUENTS AND PHARMACOLOGICAL ACTIVITIES OF TRIDAX PROCUMBENS: A REVIEW - Gubbiveeranna, Vinod; Nagaraju, S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Tridax procumbens is a plant used majorly in Indian traditional medicine. This is rich in alkaloids, steroids, carotenoids, flavonoids (such as catechins, centaurein and bergenins), fatty acids, phytosterols, tannins and minerals. Concoctions of extracts from T. procumbens leaves, stem, flower, and roots are used to treat patients suffering from diabetes, arthritis, inflammatory reactions and even applied to open wounds. The medicinal value of extracts has been evident by in vitro/in vivo assay of antioxidant, anti-bacterial, anti-inflammatory, anti-microbial, vasorelaxant, anti-leishmanial and mosquitocidal activities. Still, there is derth in the studies on isolation, characterization and evaluation of active principles from the extracts. This current review article gives comprehensive information about the T. procumbens taxonomy, morphology, geographical distribution, phytoconstituents and pharmacological activities.